Pengaruh Penambahan Kamper sebagai Aditif terhadap Karakteristik dan Emisi Gas Buang Mesin Berbahan Bakar Bensin - Nuryoto; Sobarsah, G. Awaludin; Rahmayetty, Rahmayetty; Jayanudin (BRIN Publishing (Penerbit BRIN), 2024)
Abstract The automotive industry, synonymous with motorized vehicles, has experienced rapid development, and every motorized vehicle requires fuel as its power source. To ensure optimal engine performance, some individuals add additives to fuel using camphor. Research on camphor as a fuel additive is not new, as it has been studied by several researchers before, although with the use of premium gasoline in previous studies. In this study, we observed a different type of fuel, namely